Perancangan Troli Ergonomi pada Aktivitas Pengangkutan Beras di Penggilingan Padi - Sokhibi, Akh; Alifiana, Mia Ajeng; Ghozali, Muhammad Imam (Jurnal Sistem dan Manajemen Industri, 2018)
Ergonomics in rice milling does not use often. In Kedungdowo village, Kaliwungi Subdistrict, Kudus Regency, the working position of the rice hull machine to the scales did not take into account the ergonomic aspects because only rice was rice with a shoulder. This is done continuously fast and efficiently. The method used in this study is to measure anthropometric data from rice carrying workers. The anthropometric data in this study were worker elbow height (TSB) and hand held hand diameter (DGT). Anthropometric data is processed and edited for the ergonomic trolley base to be designed. The results of the research conducted were obtained by the ergonomic trolley concept. with a height of 100, 81 cm trolley; diameter of electric hand trolley 4.77 cm; 71 cm long trolley; and the width of the trolley is 52 cm. From the results of the questionnaire, the profit that occurred on the neck was 11%, in the hand round was 90%, the back was 4%, the waist was 8%, the thigh was 47%, the knee was 25%, the calf was 17%. after using ergonomic trolleys